2004
DOI: 10.1007/s00221-003-1660-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional circuitry underlying natural and interventional cancellation of visual neglect

Abstract: A large body of work demonstrates that lesions at multiple levels of the visual system induce neglect of stimuli in the contralesional visual field and that the neglect dissipates as neural compensations naturally emerge. Other studies show that interventional manipulations of cerebral cortex, superior colliculus or deep-lying midbrain structures have the power to attenuate, or cancel, the neglect and reinstate orienting into a neglected hemifield, and even into a profound cortically blind field. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 221 publications
1
34
0
Order By: Relevance
“…A subsequent lesion of the now unconstrained and hyperactive contralesional colliculus thus removed its suppression of the ipsilesional colliculus leading to a restoration in bilateral orienting behavior. Further lesion and reversible deactivation studies have confirmed (Sprague, 1996) and extended this effect to other regions (Lomber and Payne, 2001; Payne and Rushmore, 2004). …”
Section: Estimating Nbs-driven Enhancement and Cost Within The Net-zementioning
confidence: 65%
“…A subsequent lesion of the now unconstrained and hyperactive contralesional colliculus thus removed its suppression of the ipsilesional colliculus leading to a restoration in bilateral orienting behavior. Further lesion and reversible deactivation studies have confirmed (Sprague, 1996) and extended this effect to other regions (Lomber and Payne, 2001; Payne and Rushmore, 2004). …”
Section: Estimating Nbs-driven Enhancement and Cost Within The Net-zementioning
confidence: 65%
“…However, the intermediate and deeper, motor superior colliculus seems to have a critical role in primate eye–hand coordination, and cells in this region, 98 overlapping with the mesencephalic reticular formation, may map both gaze-dependent and gaze-independent hand movements yes, OK. In animals 3436 and humans, 99,100 damage to the motor (deep) superior colliculus induced asymmetric spatial behaviour and spatial neglect, indicating that this structure could be a critical node in the spatial motor network. 1,3,15,41,101 Whether this region participates in modulation of interhemispheric balance of eye–hand movement bias during prism adaptation, or whether it might map frontal–subcortical spatial ‘aiming’, requires further research.…”
Section: Prism Adaptation Studiesmentioning
confidence: 99%
“…The ipsilateral superior colliculus, released from intracollicular inhibition, may induce strong contralateral orienting (the Sprague effect (Sprague, 1966). Although the mechanisms of the Sprague effect have been disputed (Wallace, Rosenquist, & Sprague, 1990), a role of intracollicular inhibition in this phenomenon is supported in recent studies in cats (Payne & Rushmore, 2004; Rushmore, Valero-Cabre, Lomber, Hilgetag, & Payne, 2006) and human stroke survivors (Weddell, 2004). …”
Section: Introductionmentioning
confidence: 97%